ECOLOGICAL ASPECTS OF RIPARIAN FOREST REMNANTS IN THE SÃO JOÃO RIVER BASIN, PARANÁ - Gomes, Juliana; Silva, Adriane Ribeiro; Pilati, Bruna; Andrade, Anna Luiza Pereira; Fragoso, Rosimeri de Oliveira; Carmo, Marta Regina Barrotto (Floresta, 2021)
Riparian forests are those that accompany waterways, forming natural corridors with great biological importance in the environments in which they are inserted. Thus, due to the relevance of these areas, this study aimed to increase information about riparian forest remnants located in the São João River basin, Paraná, to subsidize the ecological diagnosis of vegetation and to determine conservation and restoration actions for the area, as well as for its use in future management plans. In this study, woody species in the upper (CBH ≥ 15cm) and lower (CBH ˂ 15cm and height ≥ 2m) strata were sampled using the quadrants method from eight collection stations along the São João River. Based on the floristic survey and phytosociological parameters observed, it was possible to verify that the riparian forest remnants are quite degraded, presenting a majority of plants that are common in early stages of succession, due to surrounding anthropic actions. On the other hand, the analysis of reproductive attributes revealed the existence of flowering and fruiting species throughout the year, as well as a high number of zoophilic and zoochoric plants, attributes essential for maintaining ecological processes and ensuring ecosystem services. Conservation and restoration actions are needed in this area to reduce the effects of landscape fragmentation, in order to provide adequate support for community development.